Derajat Merokok Dengan Disabilitas Low Back Pain Pada Tenaga Kerja Bongkar Muat Di Pelabuhan Kota Kendari - Liasyarah Marudin; rustam rustam; La Ode Alifariki; adius kusnan (Politeknik Kesehatan Makassar, 2021)
Background : Low back pain is unpleased condition or pain which can make limitation in activity and LBP is a leading cause of disability in the world. Based on data from the Port Health Office in 2018, LBP is a condition that is often experienced by loading and unloading workers in the Port of Kendari. There are many factors that can affect low back pain, one of which is smoking. This study aimed to determine the relationship of smoking degree with low back pain disability. Method : This research is an observasional analytic study with cross-sectional approach. This research is an observasional analytic study with cross-sectional approach. 130 sampels were acquired through total sampling. Data were analyzed using the Spearman correlation test (p value <0,05). Result : The result of the study showed that the majority of respondents have mild smoking habits of 70,8% and mild disabilities of 42,3%. Based on statistical test, a positive correlation was obtained between of smoking degree and low back pain disability of loading and unloading workers in port of Kendari City with p value = 0,000 and a correlation coefficient = 0.524. Conclusion : The conclusion of this study is that there is a significant correlation between smoking degree and low back pain disability of tenaga kerja bongkar muat in port of Kendari City.